2004
DOI: 10.1002/jsfa.1737
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the selenium content of bovine milk through alteration of the form and concentration of selenium in the diet of the dairy cow

Abstract: Since estimated dietary selenium intake in the UK has declined steadily from around 60 µg day −1 in 1975 to 34 µg day −1 in 1997, there is a need to increase selenium intake from staple foods such as milk and milk products. An experiment was therefore done to investigate the relationship between dietary source and concentration of selenium and the selenium content of bovine milk. In a 3 × 3 factorial design, 90 mid-lactation Holstein dairy cows were supplemented over 8 weeks with either sodium selenite (S), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
55
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 24 publications
19
55
1
1
Order By: Relevance
“…Our data showed that the above value of milk selenium concentration could be easily reached in cows fed 0.3 mg/kg DM. Givens et al (2004) did not achieve 20 mg selenium/l of milk even with dietary selenium concentrations over the maximum allowed by the 05/1459 EC Commission Regulation (European Community, 2005). …”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Our data showed that the above value of milk selenium concentration could be easily reached in cows fed 0.3 mg/kg DM. Givens et al (2004) did not achieve 20 mg selenium/l of milk even with dietary selenium concentrations over the maximum allowed by the 05/1459 EC Commission Regulation (European Community, 2005). …”
Section: Discussionmentioning
confidence: 98%
“…Our data showed a maximum level (about twofold higher than the control) already at day 3, with plateau at day 10 until the end of the trial (Figure 1b), whereas in previous works, the selenium concentrations in milk and plasma tend to remain at steady condition in about 1 to 2 weeks after supplementation (Heard et al, 2007) and reach their maximums in about 40 days (Conrad and Moxon, 1979). Givens et al (2004) report a linear relationship between milk and dietary selenium concentrations in which the milk selenium (mg/l) 5 8.03 1 12.04 diet selenium (mg/kg DM) with an r 2 5 0.96. This was not supported by our results where the dose response on milk selenium concentration was nonlinear in Experiment 1 and the milk yield was the only significative factor in Experiment 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Se supplements of 200 mg/day have shown reduced risks in the incidences of lung, prostate and colo-rectal cancers in humans (Combs, 2001a). Rayman (2000 and2004) reported that between 1975 and 1995 Se intakes within the UK decreased from around 60 to 34 mg per person/ day, which is approximately 50% of the recommended daily intake (Givens et al, 2004).…”
Section: Introductionmentioning
confidence: 99%